2010
DOI: 10.1510/icvts.2009.230029
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tumors in adults: surgical management and follow-up of 19 patients in an Australian tertiary hospital☆

Abstract: The objective of this report is to share our experience with the different types of cardiac tumors, surgical management, postoperative complications and mid-term outcome of patients in an Australian tertiary hospital. Nineteen patients underwent cardiac surgery for tumors between 2001 and 2008. Their data was prospectively collected and retrospectively analyzed. The mean follow-up was 17 months. The follow-up was 100% through telephone interviews. There were multiple presenting symptoms with shortness of breat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…Cardiac mass resection has traditionally been performed through a median sternotomy Although primary tumors of the heart are uncommon, the clinical outcomes of benign cardiac tumors, especially cardiac myxoma, carry an excellent prognosis, and recurrence is infrequent [1][2][3]. Reports of minimally invasive valve surgery have been published since the 1990s [4,5], and the minimally invasive approach for cardiac surgery has become gradually more accepted during recent years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac mass resection has traditionally been performed through a median sternotomy Although primary tumors of the heart are uncommon, the clinical outcomes of benign cardiac tumors, especially cardiac myxoma, carry an excellent prognosis, and recurrence is infrequent [1][2][3]. Reports of minimally invasive valve surgery have been published since the 1990s [4,5], and the minimally invasive approach for cardiac surgery has become gradually more accepted during recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary tumors of the heart are uncommon, with recent developments in surgical technique and diagnostic technology such as echocardiography, tumor resection carries a favorable prognosis [1,2]. The most common cardiac tumor is atrial myxoma, which is reported to account for approximately 40-90 % of all primary cardiac tumors [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately one‐quarter to one‐third of all primary heart and pericardium tumors are malignant. But available data from single‐center studies vary, and the reported prevalence is between 3% and 28.7%, as shown in Table . With the exception of mesothelioma, or primary malignancy of the pericardium, primary malignancy of the heart consists of different sarcomas and lymphomas …”
Section: Introductionmentioning
confidence: 99%
“…Complete or partial excision of primary or metastatic cardiac sarcoma can provide hemodynamic improvement and relief from congestive heart failure. Postsurgical adjuvant radiation and chemotherapy have not proven consistently beneficial [13,14]. However, they can be beneficial in improving the symptoms and quality of life.…”
Section: Discussionmentioning
confidence: 99%